Bicyclic Peptide Inhibitor of Urokinase‐Type Plasminogen Activator: Mode of Action. Issue 16 (2nd October 2013) - Roodbeen, Renée; Paaske, Berit; Jiang, Longguang; Jensen, Jan K.; Christensen, Anni; Nielsen, Jakob T.; Huang, Mingdong; Mulder, Frans A. A.; Nielsen, Niels Chr.; Andreasen, Peter A.; Jensen, Knud J.
Abstract The development of protease inhibitors for pharmacological intervention has taken a new turn with the use of peptide‐based inhibitors. Here, we report the rational design of bicyclic peptide inhibitors of the serine protease urokinase‐type plasminogen activator (uPA), based on the established monocyclic peptide, upain‐2. It was successfully converted to a bicyclic peptide, without loss of inhibitory properties. The aim was to produce a peptide cyclised by an amide bond with an additional stabilising across‐the‐ring covalent bond. We expected this bicyclic peptide to exhibit a lower entropic burden upon binding. Two bicyclic peptides were synthesised with affinities similar to that of upain‐2, and their binding energetics were evaluated by isothermal titration calorimetry. Indeed, compared to upain‐2, the bicyclic peptides showed reduced loss of entropy upon binding to uPA. We also investigated the solution structures of the bicyclic peptide by NMR spectroscopy to map possible conformations. An X‐ray structure of the bicyclic‐peptide–uPA complex confirmed an interaction similar to that for the previous upain‐1/upain‐2–uPA complexes. These physical studies of the peptide–protease interactions will aid future designs of bicyclic peptide protease inhibitors.